Analysis of injury incidences in the Korea national men`s soccer teams - Kwan, H.-B.; Chang-Hwa, J. (Journal of Exercise Rehabilitation, 2019)
The purpose of this study was to identify the frequency and characteristics of injuries that occurred during the training camps and matches of the national soccer teams (under-20 [U-20], under-23 [U-23], A men`s national teams). The research data were based on injuries that occurred from January 2016 to December 2017. The athletic trainer, a member of the Korea Football Association, recorded injuries based on the recording sheet of the Asian Football Confederation Daily Medical Report. A total of 1,689 (984 in 2014; 705 in 2017) injuries were reported for the 2 years. Most injuries were sports injuries (95%, sprains, etc.), and other conditions such as respiratory, digestive, and ocular, comprised only 5% of cases. The most injured areas of the national team players were the lower limbs (85%, 1,366). The frequency of the head/trunk and upper extremity injuries were relatively low (8.4%, 135; 6.5%, 105). The frequency of injuries according to positions were as follows: midfielder (40.3%, 648), defender (36.6%, 688), forward (17.8%, 286), and goalkeeper (5.2%, 84). The most common types of injuries were contusions (37.3%, 599), followed by muscle rigidity (29.0%, 466) and sprains (16.8%, 270). The characteristics of injuries amongst national soccer teams, according to age, were similar, but the injury characteristics for each position were different. Therefore, when organizing training programs for prevention and rehabilitation of athlete injuries and improvement of performance, it is necessary to consider the performance characteristics of each position.